Geometry of cycling track - Solarczyk, Maciej Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The paper describes the problems related to shaping of geometry of the cycling track. The method of selection of the angle at the track arch is presented. Issues related to the selection of the appropriate transition curve and the superelevation ramp along the transition curve are presented. Reference to the recommendations presented in the literature and scientific papers has been made. Special attention to the need of consideration of the subjective feelings of the cyclist is paid. The paper describes the guidelines of the International Cycling Union (UCI) on shaping of geometry of the cycling track.